PENGARUH TERAPI TERTAWA TERHADAP TINGKAT ANSIETAS PADA LANSIA DI WILAYAH KERJA PUSTU LINGGAR JATI PLAJU KOTA PALEMBANG - Mareta Akhriansyah; Raden Surahmat; Nuriza Agustina; Amalia Amalia (Jurnal Kesehatan Medika Saintika, 2025)
Becoming elderly is a scientific process that begins at the start of life. Elderly individuals are not always able to live independently; they often require care and seek to remain beneficial to themselves and their surroundings. Aging is a natural process that can cause anatomical and physiological changes, which may affect bodily and psychological functions and capabilities. One common psychological issue among the elderly is anxiety. A non-pharmacological therapy that can be used to reduce anxiety is laughter therapy. This study aims to determine the effect of laughter therapy on anxiety levels among the elderly in the working area of Pustu Linggar Jati Plaju, Palembang City. The research method used is a Pre-Experimental Design with a One Group Pretest-Posttest approach. The sampling technique used is purposive sampling, with a total of 34 respondents. In this study, the anxiety levels of the elderly were measured before and after laughter therapy was administered. The results showed a significant decrease in anxiety levels (p-value < 0.05), with the median value dropping from 26.50 to 15.50. This indicates that laughter therapy can reduce anxiety in the elderly. It can therefore be concluded that laughter therapy has an effect on anxiety levels in the elderly at Pustu Linggar Jati Plaju, Palembang. It is hoped that the implementation of non-pharmacological approaches like laughter therapy can help alleviate anxiety in the elderly.